Perceptions on using the International Caries Detection and Assessment System (ICDAS) among Malaysian private dentists: a qualitative study - Tan, Wen Wu; Lin, Galvin Sim Siang; Hashim, Hasnah (Brazilian Dental Science, 2023)
Objective: to explore the perceptions of Malaysian private dentists on the use of the International Caries Detection and Assessment System (ICDAS) in their dental practice. Material and Methods: this qualitative study involved individual interviews with twelve general dental practitioners working in the private sector, who has been exposed to ICDAS training during their undergraduate study. Purposive sampling was carried out among private dentists in Malaysia from various states to reflect diversity. The interviews were recorded and transcribed. Data analysis was conducted by thematic analysis. Results: five main barriers were identified through the coding process, namely time factors, lack of training, having no effect on treatment planning, charting difficulties, and low patient awareness on prevention. Better training and a strong requirement by the authorities to use this system were identified as the enabling factors. Conclusion: private dentists in Malaysia encountered a myriad of challenges in adopting the ICDAS index. Hence, it is necessary to provide adequate training and assistance in understanding the benefits of utilizing the ICDAS system, and computerization of data input. KEYWORDS Dental caries; Dental education; Dentists; Patient care; Qualitative research.